223k views
1 vote
-7h+3(4-6h)=127 is h= 25?

1 Answer

5 votes

Answer:

No, h = (-23)/5

Explanation:

Solve for h:

3 (4 - 6 h) - 7 h = 127

3 (4 - 6 h) = 12 - 18 h:

12 - 18 h - 7 h = 127

-18 h - 7 h = -25 h:

-25 h + 12 = 127

Subtract 12 from both sides:

(12 - 12) - 25 h = 127 - 12

12 - 12 = 0:

-25 h = 127 - 12

127 - 12 = 115:

-25 h = 115

Divide both sides of -25 h = 115 by -25:

(-25 h)/(-25) = 115/(-25)

(-25)/(-25) = 1:

h = 115/(-25)

The gcd of 115 and -25 is 5, so 115/(-25) = (5×23)/(5 (-5)) = 5/5×23/(-5) = 23/(-5):

h = 23/(-5)

Multiply numerator and denominator of 23/(-5) by -1:

Answer: h = (-23)/5

User Udaya Sri
by
7.0k points